IMPACT OF COVID-19 QUARANTINE ON CHILD SEXUAL ABUSE: EXPERIENCE OF CHILD ADVOCACY CENTER - Hatice Oksal; Ömer Büber; Alper Alnak; Hüseyin Zahid Kara (İstanbul Tıp Fakültesi Dergisi)
Objective: We aimed to evaluate the characteristics of child sexual abuse reports and the affecting factors during the pandemic compared to the pre-pandemic period. Material and Method: The study included 506 children and adolescents admitted to the Child Advocacy Center (CAC). Case and control groups were determined according to the time of admission (first 15 months of the pandemic and 15 months before the pandemic). The data were obtained by retrospectively examining the files, forensic investigation reports, family evaluation reports, and other documents in the files of the children in the legal process. Result: Cases applied to CAC during the pandemic decreased by 16 percent. Sexual abuse reported by teachers and professionals such as public servants decreased from 30% to 4.7%. However, abuse through online platforms doubled. Finally, recurrent domestic abuse increased significantly during quarantine (p<0.001). Conclusion: The pandemic changed the way CAC is admitted and the specifics of abuse. The teachers and public servants reported fewer incidences of sexual abuse during the pandemic period. In addition, the form of abuse shifted to the online platform, and recurrent domestic abuses have increased. Professionals working in the field of sexual abuse should keep in mind that the possible effects of these changes may continue after the pandemic.